PERSEPSI MASYARAKAT TERHADAP LOKASI PASAR BARU BOBOU KELURAHAN FAOBATA KECAMATAN BAJAWA KABUPATEN NGADA - Meo, Praksedis Stigma; Luciany, Yohanes Paulus (JURNAL EQUILIBRIUM, 2021)
This study aims to determine how the community's perception of the Pasar Baru Bobou location. This research is a qualitative descriptive study, which explains or describes the results of the research based on the data obtained from the research results. The population in this study are people in 7 sub-districts, and traders who sell in the market. The sampling technique used purposive sampling method, namely the community and traders as market users. The population in this study amounted to 179 people consisting of 140 people and 39 traders. The data collection technique uses a questionnaire or questionnaire which contains statements and summarized in tables and graphs and explains them according to the results of the interview. The results of this study indicate that the relocation of the Bajawa Inpres Market to Pasar Baru Bobou resulted in many community complaints. In general, the results of research in 7 urban villages describe the community as agreeing with the market relocation. However, the community complained about the cost of transportation to the Bobou market. They said that the transportation costs were very expensive, up 100-200% from usual. Meanwhile, for traders, they complained about the availability of water in the market. Therefore, the recommendation given to the government regarding public complaints is that the government needs to provide free vehicles for the community, at least free vehicles in the city as transportation to the market if government funds allow. Meanwhile, for traders, the government must pay more attention to the availability of water in the market.